Integrated system for e-health advisory web services provision using broadband networks. (29th September 2008) - Sakkopoulos, Evangelos; Sourla, Efrosini; Tsakalidis, Athanasios; Lytras, Miltiadis D.
In this work an integrated system of electronic reports of laboratorial examinations results from electronic ultrasonograph and cardiotokograph, documents exchange and health advisory services provision is presented. The integrated system was developed for the private maternity hospital of Patras under the action "Medical Enterprises Financing for Specialized Informatics Applications Provision and Installation" of 'Information Society'. Its aim is to supply enhanced health services and information exchange services among health services provision organisations. Benefits from its usage are the direct exploitation of the enhanced Health Services and the cooperation and interaction between health organisations.